Highly Defective Layered Double Perovskite Oxide for Efficient Energy Storage via Reversible Pseudocapacitive Oxygen‐Anion Intercalation. Issue 11 (2nd January 2018) - Liu, Yu; Wang, Zhenbin; Veder, Jean‐Pierre Marcel; Xu, Zhenye; Zhong, Yijun; Zhou, Wei; Tade, Moses O.; Wang, Shaobin; Shao, Zongping
Abstract: The use of perovskite materials as anion‐based intercalation pseudocapacitor electrodes has received significant attention in recent years. Notably, these materials, characterized by high oxygen vacancy concentrations, do not require high surface areas to achieve a high energy storage capacity as a result of the bulk intercalation mechanism. This study reports that reduced PrBaMn2 O6– δ (r‐PBM), possessing a layered double perovskite structure, exhibits ultrahigh capacitance and functions as an excellent oxygen anion‐intercalation‐type electrode material for supercapacitors. Formation of the layered double perovskite structure, as facilitated by hydrogen treatment, is shown to significantly enhance the capacitance, with the resulting r‐PBM material demonstrating a very high gravimetric capacitance of 1034.8 F g −1 and an excellent volumetric capacitance of ≈2535.3 F cm −3 at a current density of 1 A g −1 . The resultant formation of a double perovskite crystal oxide with a specific layered structure leads to the r‐PBM with a substantially higher oxygen diffusion rate and oxygen vacancy concentration. These superior characteristics show immense promise for their application as oxygen anion‐intercalation‐type electrodes in pseudocapacitors. Abstract : The formation of a double perovskite crystal oxide with a specific layered structure results in the reduced PrBaMn2 O6‐ δ (r‐PBM) with a substantially higher oxygen diffusion rate and oxygen vacancy concentration. These factors are highly beneficial to the oxygen vacancies as charge storage sites can be applied in the pseudocapacitors with an oxygen ion intercalation process.